Examining the need for a metaverse-based blended learning module in college English: insights from Southwest China - Yuliang Jiao; Rafiza Abdul Razak; Dorothy DeWitt (Journal of Education and Learning (EduLearn), 2026)
Although English is an important language for globalization and innovation, Chinese students lack the proficiency in the language, which might be attributed to the lack of engagement. Further, as immersive technologies can enhance learning, this study investigates the perceptions and readiness of integrating metaverse-based blended learning (MBBL) modules in college English curricula. A survey among 380 undergraduate students in southwestern China using a questionnaire was conducted to determine their learning preferences and technological readiness. Findings indicate that students needed more engaging and interactive activities, preferring collaborative and simulative learning environments. Despite limited familiarity with metaverse technologies, students demonstrated technological readiness. Hence, the results suggest that a MBBL to enhance English as a foreign language (EFL) education could be implemented. This study provides empirical evidence to inform the design of a metaverse-based technologies in EFL instruction for innovation in tertiary language pedagogy. Future studies could design such a module for implementation and evaluation.